Lagenidium callinectes INFECTION ON ROTIFERS Brachionus sp. - Des Roza; Fris Johnny (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2007)
Milkfish, Chanos chanos and humpback grouper, Cromileptes altivelis hatcheries have developed at Gondol, Bali since 1995 and until now still rely on rotifers, the main natural food, supply. Recent problem on mass culture of rotifer, Brachionus sp. is harvest failure caused by fungus infection. Under light microscope, infected eggs and bodies of the rotifers was filled with numerous aseptate hyphae. Two isolates of fungi were isolated from rotifer eggs and carcass on June 21st, 2004 and on June 25th, 2004 obtained from milkfish and humpback grouper hatcheries at Gondol. Based on its morphological characteristics, the pathogenic fungus was identified as Lagenidium callinectes which grows optimally at 25°C and survives in 1.0%, 2.5%, and 5.0% NaCl as well as in 1.0% and 2.5% KCl. Both of the present isolates utilize only 8 out of 26 carbohydrates and derivatives tested as carbon, nutrition and energy sources. This finding is the first report on rotifer, Brachionus sp. infected with L. callinectes causing up to 100% mortality.